Dissecting dormancy and quiescence in hematopoietic stem cells - Ibneeva, Liliia; Grinenko, Tatyana (Frontiers in Hematology, 2024)
Quiescence is a fundamental state of adult hematopoietic stem cells (HSCs) characterized by their residence in the G0 phase of the cell cycle. Despite being quiescent, HSCs retain their capacities for self-renewal and multipotency, enabling them to produce all blood lineages. Recent discoveries have shown that HSCs can dive into an even deeper state of quiescence with a very low division rate in steady-state conditions, known as dormancy. Dormant HSCs (dHSCs) have the most superior stem cell properties among HSCs, placing them at the top of the hematopoietic hierarchy. In this review, we argue that quiescence and dormancy are not synonyms in the context of HSCs. Specifically, dHSCs constitute a unique reserve pool of HSCs, mobilized only under stress conditions to protect the HSC compartment throughout life. While HSC quiescence is well-studied, the molecular features of HSC dormancy remain less well-defined. We will discuss the available methods for dHSC isolation and summarize the latest findings on the roles of niche factors, transcription factors, chromatin regulators, and cell cycle-related proteins in maintaining HSC dormancy. Additionally, we will explore whether insights from the quiescent HSC research can be applied to dHSCs. Lastly, we will assess the therapeutic potential of utilizing or targeting dHSCs to improve stem cell transplantation outcomes and treat hematological diseases, opening new avenues for research and clinical applications in regenerative medicine and oncology.